Study on coal seam physical characteristics and influence on stimulation: A case study of coal seams in zhengzhuang block - Lu, Yanjun; Han, Jinxuan; Zhang, Hua; Xu, Zhenping; Yang, Zhaozhong; Yang, Manping; Guo, Junfeng; Zhu, Hongjian; Qi, Yu (Frontiers in Earth Science, 2023)
Coalbed Methane (CBM) is an unconventional form of natural gas which is self-generated and self-stored in coal seams. In order to realize the effective exploitation of CBM in Zhengzhuang block, microstructure, wettability, permeability, rock mechanics and in-situ stress of coal were studied in this research. It is found that high rank anthracite characterized by high vitrinite content and low inorganic mineral content, is abundant in CBM. More than 96% of inorganic minerals are clays dominated by kaolinite and illite. Various types of pores are developed on the coal. The wettability of coal differs from high to low to surface water, active water, and foam fracturing fluid; and contact angles of coal with active water and foam fracturing fluid decrease with the increase of burial depth. Gradients of fracture pressure and closure pressure in No.3 coal seam are higher than that of No.15 coal seam. The elastic modulus of coal is lower than that of sandstone. The construction curve of hydraulic fracturing shows that, when the construction flow rate and sand quantity are similar, the construction pressure of prepad in No.3 coal seam is lower than the pumping pressure of No.15 coal seam, but the propagated pressure is higher than that of No.15 coal seam. The drainage effect of No.3 coal seam with large pore volume, shallow burial depth and obvious fracture pressure is better than that of No.15 coal seam. The comprehensive understanding of coal physical properties and engineering practice in the block provide certain guiding significance to the CBM exploitation in Qinshui Basin.